Consumers' Attitude towards Online Shopping in Janakpurdham (Journal of Management, 2021)
The paper aims to explore about the use of Internet that changes the way consumers purchase goods and services. The growing number of internet users in Nepal provides a bright prospect for online shopping. Recent research has shown an interest in investigating the factors that affect the attitude of consumers towards online shopping. The study is being carried out to identify and analyze the factors that affect consumers' attitude towards online shopping in Janakpurdham and to examine the factors that motivate consumers to shop online. In this study, quantitative research method has been used. Questionnaire method is used to collect the data. The study has been done by convenient sampling method. The main finding of this study is that among the four factors (convenience, website design/features, time saving and security) selected for this research, the most attractive and influencing factor for online shopping is convenience, followed by time saving the second and thirdly security. Results have also showed that the website design/features are also important for online shopping. The findings also indicate that time saving is the most important factor that motivate consumers to shop online, followed by easy to purchase second and thirdly variety at one shop. This study is useful to understand the online shopping behavior of consumers.